2014
DOI: 10.1186/2049-9957-3-31
|View full text |Cite
|
Sign up to set email alerts
|

Mass drug administration for lymphatic filariasis elimination in a coastal state of India: a study on barriers to coverage and compliance

Abstract: BackgroundLymphatic filariasis is targeted for elimination in India through mass drug administration (MDA) with diethylcarbamazine (DEC) combined with albendazole (ABZ). For the strategy to be effective, >65% of those living in endemic areas must be covered by and compliant to MDA. Post the MDA 2011 campaign in the endemic district of Odisha, we conducted a survey to assess: (i) the filariasis knowledge in the community, (ii) the coverage and compliance of MDA from the community perspective, and (iii) factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
91
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(98 citation statements)
references
References 14 publications
5
91
0
2
Order By: Relevance
“…At present, countries implementing MDA for schistosomiasis control are still struggling to attain the ideal level of coverage (75%). Increased awareness, understanding of disease, and treatment options have been linked to good coverage rates and compliance with MDA for other NTDs (Aswathy et al, 2009;Gunawardena et al, 2007;Hussain et al, 2014). The Philippines is one of the countries with below-target national coverage rates at 43.5% in 2015.…”
Section: Discussionmentioning
confidence: 99%
“…At present, countries implementing MDA for schistosomiasis control are still struggling to attain the ideal level of coverage (75%). Increased awareness, understanding of disease, and treatment options have been linked to good coverage rates and compliance with MDA for other NTDs (Aswathy et al, 2009;Gunawardena et al, 2007;Hussain et al, 2014). The Philippines is one of the countries with below-target national coverage rates at 43.5% in 2015.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately two-thirds of the infected population remain asymptomatic, and these individuals might not be aware of the benefits of treatment 40 . Albuquerque et al .…”
Section: Discussionmentioning
confidence: 99%
“…(13) Hussain et al (10) state that failure to attain drug compliance in the MDA program is due to absence of health personnel during distribution of antifilariasis drugs. Among 99% of subjects who are recipients of antifilariasis drugs in India, only around 25% take the drugs, which agrees with the MDA program in the Pabean area of Pekalongan.…”
Section: Discussionmentioning
confidence: 99%
“…(9) Another study showed that 99% of the study participants received DEC and albendazole tablets during MDA, of which only just above a quarter actually consumed the drugs. (10) The gap between MDA coverage rates and compliance rates, as reported in previous studies, needs to be subjected to further reasearch to find the causative factors. The purpose of the present study was to assess the impact of the MDA program and determine the factors associated with noncompliance in taking antifilariasis drugs.…”
Section: Introductionmentioning
confidence: 99%